The dual and opposite role of the TM6SF2‐rs58542926 variant in protecting against cardiovascular disease and conferring risk for nonalcoholic fatty liver: A meta‐analysis - Pirola, Carlos J.; Sookoian, Silvia (Hepatology (Baltimore, Md.), 2015)
The aim of this work was to estimate the strength of the effect of the TM6SF2 E167K (rs58542926 C/T) variant on blood lipid traits and nonalcoholic fatty liver disease (NAFLD) across different populations. We performed a systematic review by a meta‐analysis; literature searches identified 10 studies. The rs58542926 exerts a significant role in modulating lipid traits, including total cholesterol (TC), low‐density lipoprotein cholesterol (LDL‐C), triglycerides (TG), and NAFLD. However, this influence on lipids and NAFLD is opposite between genotypes in the dominant model of inheritance. Pooled estimates of random effects in 101,326 individuals showed that carriers of the minor T allele (EK+KK individuals), compared with subjects homozygous for the ancestral C allele (EE genotype), are protected from cardiovascular disease (CVD), showing lower levels of TC, LDL‐C, and TG; the differences in mean ± standard error (mg/dL) are −8.38 ± 1.56, −3.7 ± 0.9, and −9.4 ± 2.1, respectively. The rs58542926 variant was not associated with high‐density lipoprotein cholesterol in a large sample (n = 91,937). In contrast, carriers of the T allele showed a moderate effect on the risk of NAFLD (odds ratio: 2.13; 95% confidence interval: 1.36–3.30; P = 0.0009; n = 3273) and approximately ∼2.2% higher lipid fat content when compared with homozygous EE (n = 3,413). Conclusions: The rs58542926 appears to be an important modifier of blood lipid traits in different populations. As a challenge for personalized medicine, the C‐allele, which has an overall frequency as high as 93%, is associated with higher blood lipids, whereas the T allele confers risk for NAFLD; in turn, CVD and NAFLD are strongly related outcomes. Although the variant confers protection against CVD at the expense of an increased risk of NAFLD, it does not explain the link between these two complex diseases.(Hepatology 2015;62:1742–1756)